Magnaporthe oryzae aminosugar metabolism is essential for successful host colonization. (19th February 2016) - Kumar, Anil; Ghosh, Sumit; Bhatt, Dharmendra Nath; Narula, Alka; Datta, Asis
Summary: Pathogens encounter and metabolize a range of host‐derived metabolites while proliferating inside the host. Our understanding of these metabolites and their metabolic processes has remained largely incomplete. We investigated the role of the M agnaporthe oryzae  N‐acetylglucosamine (GlcNAc) catabolic pathway during rice infection. The catabolic pathway is composed of a GlcNAc transporter (MoNgt1), hexokinase(s), a GlcNAc‐6‐phosphate deacetylase (MoDac) and a GlcN‐6‐phosphate deaminase (MoDeam). A detailed characterization of the Δ mongt1, Δ modac and Δ modeam null mutants revealed that a defect in GlcNAc catabolism impairs the pathogenicity of M . oryzae . These mutants showed severely reduced virulence in susceptible rice cultivar due to their inability to neutralize host‐derived reactive oxygen species and their failure to develop invasive hyphal growth within the host tissue. Interestingly, during oxidative stress, M . oryzae proliferated efficiently in GlcNAc‐containing media compared with other sugars, and the expression of fungal antioxidant genes was upregulated following GlcNAc treatment. However, GlcNAc inhibited the growth of the Δ modac and Δ modeam mutants, and this growth inhibition was enhanced during oxidative stress. These results suggest that GlcNAc helps fungus to overcome oxidative stress inside its host, perhaps by activating an antioxidant defence. In the absence of a functional catabolic pathway, GlcNAc becomes toxic to the cells.